The relationship of political settlement analysis to peacebuilding from a feminist perspective. (3rd May 2016) - Ní Aoláin, Fionnuala
Abstract: In the policy literature addressing bilateral state engagement with fragile, conflicted or weakened states, the language of 'political settlement' appears increasingly ubiquitous. But much of the emerging literature is gender blind, and there is little by way of comprehensive scholarly or policy literature available to elucidate the gender dimensions of political settlement. This article explores both how the definition of 'political settlement' functions to include or exclude women both formally and informally, and how emergent 'political settlement' theory and practice can both build on peace agreement analysis and avoid some of its gendered pitfalls. I ask how political settlement analysis works (or does not work) in practice to address women's needs, demands and challenges. Specifically, I explore the kinds of gendered fault lines that have emerged and settled in political settlement practice, and explore insights from law, political science and international relations that might advance women's interests.